Female Goldeneye Ducks (Bucephala clangula) Do Not Discriminate among Male Precopulatory Display Patterns - Dane, Benjamin; Harris, Rebecca; Reed, J. Michael (Tufts Archival Research Center, 2005)
Female goldeneyes remain motionless on the surface of the water while single males circle them performing a series of highly stereotyped displays. After performing between eight and 90 of these displays the male either copulates or attempts to copulate with the female. However, females allow only 58% of males to mount them, while rejecting 42%. We have examined 804 of these precopulatory sequences containing 11,841 actions in an effort to determine why females find some display sequences of males unsuitable, while others are accepted. Males have an extraordinarily varied sequence of actions, and sequence variation leading to successful and unsuccessful copulation attempts was similar. Most surprising was the tendency of males to eliminate one of the five actions, whether in successful or unsuccessful attempts. As unlikely as we think it might be as the result of natural selection, the only statistically significant difference we found between successful and unsuccessful attempts was the reduction in the frequency of expression of one or more of the behaviors in successful attempts. These observations, coupled with the large variation seen in most sequences, suggest that there is not a correct sequence, or even a correct set of actions leading to copulation. The male must, however, perform goldeneye species- specific precopulatory behavior as performed by adult males, although it apparently can be performed in a wide variety of patterns.